Tinder use among pakistani adults: a socio-psychological need perspective - Sohail, Syeda Aresha; Mahmood, Qasim; Khan, Mohsin Hassan; Gull, Zarmina (Jurnal Studi Komunikasi, 2019)
It is embedded in human nature to socialise with others. There are countless dating apps and websites that people benefit from; some may be for hook-up purposes, while others are solely for marriage. One of the most popular online dating apps in use nowadays is Tinder, which is simple and straight forward to use. People tend to seek out potential partners for all sorts of reasons; everyone has their agendas and needs to fulfil. Some may look for a long-lasting healthy relationship while others might look for a fling. It is in this context that this research seeks to investigate how the Uses and Gratifications theory helps to understand the usage patterns of the people who seek refuge in online dating, with particular focus on the use of Tinder in Pakistan. The research is based on a survey conducted from three major cities of Pakistan: Islamabad, Lahore and Karachi, where the maximum number of Tinder-users was reported. The respondents were between the ages of 18-40. Majority of the users identified themselves as Muslims. The survey results conveyed that the majority of the users use Tinder to gratify their needs, which include forming relations, getting sexual desires fulfilled, making friends and spend their time after a busy day. The findings reveal that the respondents of the study used this app for their psychological needs, such as finding someone talk to when they are lonely and for their social needs as well, such as making friends and meeting new people to increase their social circle.